Ring-opening polymerization of 19-electron [2]cobaltocenophanes: a route to high-molecular-weight, water-soluble polycobaltocenium polyelectrolytes. - Mayer, U; Gilroy, J; O'Hare, D; Manners, I (2009)
Water-soluble, high-molecular-weight polycobaltocenium polyelectrolytes have been prepared by ring-opening polymerization (ROP) techniques. Anionic polymerization of a strained 19-electron dicarba[2]cobaltocenophane followed by oxidation in the presence of ammonium chloride resulted in the formation of oligomers with up to nine repeat units. Thermal ROP of dicarba[2]cobaltocenophane followed by oxidation in the presence of ammonium nitrate resulted in the formation of high-molecular-weight polycobaltocenium nitrate, a redox-active cobalt-containing polyelectrolyte.